Extended Value Added Intellectual Coefficient Plus (E-Vaic Plus) for the Development of Shari'a Banking Intellectual Capital - Neny Tri Indrianasari; Sochib Sochib; Riza Ramadhan (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This study examines and analyzes the Intellectual Capital Development of Islamic Banking withE-VAIC Plus. The various and different findings and results from research on the measurement of Intellectual Capital provide an opportunity to test and analyze various factors that influence the measurement of Islamic banking Intellectual Capital. The variables used to test the model in this study are using VAICE-VAIC Plus uses four components, namely HCE, SCE, RCE, and CEE. This research includes causality research. The population in this study were 24 BPRS in East Java Province. The data collection technique uses a documentation study by collecting secondary data, recording, and processing data related to this research. The data used includes: published bank financial reports from 2015 to 2022.Research results foundhuman capitaldoes not affect the profitability of increasing human capital will not necessarily provide good profitability because in managing human capital must be adjusted to the competence of human resources owned, and the factor of competition from similar companies. Structural capital has no effect on profitability. This shows that to create Value Added (VA), a combination of Human Capital (HC) and Structural Capital (SC) is not needed. So that the higher the value of Structural Capital Efficiency has no effect on Return On assets. Capital Employed Efficiency affects profitability, this is because banking companies tend to use physical capital, so that the capital used can affect profitability